O simbolismo das identidades naufragadas no território Cantuquiriguaçu - Rampazo, Adriana Vinholi (2009)
Energy policies in Brazil have always favored the construction of hydroelectric power plants, considered less expensive than most other forms of energy production. In Cantuquiriguaçu, an area in the mid-west of Paraná, seven power plants were built. On Iguaçu River alone, which borders the region to the South, four large power plants are operational, having caused social and environmental impacts on the region, such as the compulsory displacement of riverside populations to make way for the reservoirs. This paper aims at understanding how the compulsory displacement of the population for the construction of Salto Santiago Power Plant, in Catuquiriguaçu territory, has forced the creation of a new meaning of this population's universe, allowing transformations in their identity. To this end, historical conceptions of the subject, and different theories of identity construction are initially discussed, without adhering to one specifically. It is understood that discussing subject formation and identity implies considering different views on the theme, as concepts have changed in modernity, although not always becoming lost. They remain important and still help in understanding identity today. They are not discarded, but updated for this study. Besides understanding about identity, it is necessary to understand Brazilian energy policy, from the developmentist period until present day, as it ensures the system of power plant implementation in the country. The main argument against the construction of hydroelectric power plants - the impact it causes on riverside populations - is discussed. Research conducted in different areas of knowledge, such as Engineering, Social Sciences, Anthropology and History, is helpful, as it shows that, when dealing with hydroelectric power plants, social and environmental interests are a secondary consideration, rejected in favor of economic interests. Thus the first part of the paper is concluded, forming the empirical and theoretical framework, which allows the formation of the research questions and the interpretation of collected data. The second part of the paper specifically focuses on the research object. Historical and cultural facts about the Cantuquiriguaçu territory are collected, intended to describe how the population that lives on the margins of Salto Santiago reservoir was formed and, at the same time, learn more about the power plants installed in that area and the compulsory movements they caused on riverside populations. Finally, based on history, as told by the riverside population and by institution representatives, the paper shows how the (re)construction of people's identities in the territory came about. As Gadamer's hermeneutics is employed to interpret data collected through oral history and documentation, the paper attempts to interconnect the objective with the subjective. Thus it is possible to understand how the construction of Salto Santiago Power Plant and the ensuing displacement of part of the riverside populations has produced modifications to their identities, due to the entry of new institutions.